THE ASPECTS OF SUSTAINABLE ECOLOGICAL AND ECONOMIC DEVELOPMENT OF THE REGION - Savin, Yu. L.; Prykhodko, O. P.; Savin, L. S.; Skrypchenko, M. M. (Science and Transport Progress, 2007)
Main aspects firm ecological-economic development of the region is described in article. Brought main ecological problems, reasons of their origin. Stated possible ways of the decision existing ecological problems of the region.